Penerapan Teknologi Informasi Dan Komunikasi Sebagai Media Interaksi Guru-Siswa - Sigit Wiranto (Jurnal VARIDIKA, 2014)
The purpose of this study is to describe the application of information and communication technology as an interactive media for teacher and student in SMPN 1 Arjosari Pacitan. This is a qualitative research. This study used an ethnographic approach. This research took place in SMP 1 Arjosari Pacitan. Interviewees in this study were the Headmaster, Head of ICT Laboratory, Administrative staff, teachers and students. Col- lecting data used observations, interviews and documentation. The validity of the data was examined by using data triangulation.Data analysis used Milles and Huberman ver- sion employ data reduction, data drawing and conclusions and verification. The results in SMPN1 Arjosari showed that: (1) The development of the application of ICT still at the stage of Application. It is characterized by the educators and teachers who have been using Information Technology for tasks related to the management of school learning activities, however their use is not optimal. This school has not been able to maximize the implementation of ICT in learning. (2) The use of ICT in the assessment of learning outcomes is limited to the preparation administration course, not the process. Though the use of IT in learning outcomes assessment will provide a transformative experience for students. (3) There are three conditions which may encourage the application of ICT in learning and assessment at this school, Facilities and infrastructure are equiped with ICT, teachers are qualified as most are already certified educators, schools can choose to suit his students and undergone the implementation the implementation of Curriculum 2013 while threats factors are: the average age of teachers is more than 40 years so that spirit for self development is less encourging began to decline, the low economic back- ground of students, speed internet access which is not adequate, and the lack of special- ized personnel who handle ICT.